Factors Affecting the Nutritional Status of School Age Children 6-12 Years Old in Raja Maligas Village, Hutabayu Raja District, Simalungun Regency 2022 - Sri Wahyuni Tarigan (Institute of Computer Science (IOCS), 2022)
This type of research uses quantitative research, with a cross-sectional study approach, namely studying the dynamics of the relationship or correlation between risk factors and impacts, the approach used is observation at a certain time.The population of this study is mothers who have school children 6-12 years old in the village ofKing Maligas Iwith a population of about 80 people. Nutrition is one of the determinants of the quality of human resources. Malnutrition will cause failure of physical growth and intelligence development, reduce work productivity and reduce body resistance which results in increased morbidity and mortality (Directorate of Nutrition RI, 2004).There is a relationship between feeding patterns and the nutritional status of school-aged children 6-12 years in Raja Maligas I Village, Hutabayu Raja District, Simalungun Regency, which is 0.015. There is a relationship between the family environment and the nutritional status of school-aged children 6-12 years in Raja Maligas I Village, Hutabayu Raja District, Simalungun Regency, which is 0.001. There is a relationship between family education (mother) and the nutritional status of school-aged children 6-12 years in Raja Maligas I Village, Hutabayu Raja District, Simalungun Regency.that is 0.006.